Parental influences on primary school children's mathematics achievements: Insights from the Longitudinal Study of Australian Children - MacDonald, A; Carmichael, Colin (My University, 2014)
Results from international mathematics tests are focussing the attention of national leaders on the learning of mathematics in the primary years. With this attention, comes the need to explore factors that contribute to and impede this learning. Though much of this focus is on classroom practices, it is timely to examine the important influence that parents have on their children's achievement. This paper reports on a secondary analysis of data from a large longitudinal study in Australia and in particular the effectiveness of Australian parents' involvement in their children's homework. Results suggest that actual help with homework has, on average, a negative effect on children's achievement even after controlling for earlier achievement. Significantly, however, other types of involvement such as the provision of a good home environment have positive effects on achievement. Implications of these findings are discussed.
International Journal of Primary, Elementary and Early Years Education
Keywords: Education and Training -- Primary; Child Development; Children -- Outcomes; Childhood and child development; Learning, education and training; Education and Training; Child Development; Children; Primary; Outcomes; Learning, education and training; Childhood and child development